Semilla de maldad - Brooks, Richard, 1912-1992 (Madrid Warner Bros, 2005)
A new English teacher at a violent, unruly inner-city school is determined to do his job, despite resistance from both students and faculty
Audio : Castellano, inglés, alemán. con varios subtítulos
Glenn Ford, Anne Francis, Louis Calhern
No apta para menores de 7 años
Keywords: Películas cinematográficas -- DVD